FOLFIRI-bevacizumab as a second-line treatment for advanced biliary tract cancer after gemcitabine-based chemotherapy - Roussot, Nicolas; Vincent, Julie; Palmier, Remi; Constantin, Guillaume; Bengrine, Leila; Fumet, Jean-David; Ghiringhelli, François (Frontiers in Oncology, 2023)
Background Advanced biliary tract cancer (BTC) has a poor prognosis. Gemcitabine with platinum chemotherapy was the standard first-line chemotherapeutic regimen until the recent addition of anti-PD-1/PD-L1 antibodies. After disease progression, the only second-line chemotherapy that has demonstrated a survival benefit versus supportive care is FOLFOX (folinic acid, fluorouracil, and oxaliplatin), with a modest benefit. This study aimed to assess the efficacy and safety of second-line FOLFIRI (folinic acid, fluorouracil, and irinotecan) combined with bevacizumab for advanced BTC. Methods This single-center retrospective study enrolled patients with metastatic BTC (intrahepatic cholangiocarcinoma [ICC], extrahepatic cholangiocarcinoma [ECC], or gallbladder carcinoma) that progressed after first-line gemcitabine-based chemotherapy. FOLFIRI-bevacizumab was administered intravenously every 2 weeks [folinic acid 200 mg/m², fluorouracil 400 mg/m² (bolus), fluorouracil 2400 mg/m² (46-h continuous intravenous infusion), irinotecan 180 mg/m², and bevacizumab 5 mg/kg] until unacceptable toxicity, patient refusal, or disease progression. Results Overall, 28 patients received the FOLFIRI-bevacizumab regimen after gemcitabine-based chemotherapy. The median overall survival (OS) was 9.0 months (95% CI 6.4–16.5). The OS rate was 39.3% (95% CI 24.8–62.3) and 10.7% (95% CI 3.7–32.1) at 12- and 24-months respectively. The median progression-free survival (PFS) was 5.2 months (95% CI 3.1–10.2) with FOLFIRI-bevacizumab. The PFS rates at 12 months and 24 months were 17.9% (95% CI 8.19–39.5] and 10.7% (95% CI 3.7–31.2), respectively. The overall response rate (ORR) to FOLFIRI-bevacizumab was 23.1%, with a disease control rate (DCR) of 69.3%. Grade 3-4 adverse events (sAE) were reported in 20 patients (71.4%) treated with FOLFIRI-bevacizumab. Conclusion FOLFIRI-bevacizumab as a second-line treatment for advanced BTC after gemcitabine-based chemotherapy showed efficacy and safety with a promising tumor response rate in this retrospective single-center study.